The Intramuros of Anak Dalita, the Looban of Manila Noir - Cristobal, Geronimo (Archīum Ateneo, 2021)
This article examines Lamberto Avellana’s Anak Dalita (LVN Pictures; 1956) as a crime melodrama that places Intramuros; Manila’s historic walled city; within the cinematic urban geography of film noir. It probes the film’s representation of the transformation of Intramuros from a colonial city of cathedrals and mansions to a post-war ruin associated with squatters and urban poverty. Situating Anak Dalita within the context of the reconfiguration of Manila’s urban space in the two decades that followed the Second World War; this essay interprets the film’s narrative about a disabled veteran’s quest to regain his self-worth in Intramuros as an allegory of post-war urban rehabilitation. The looban (meaning interior space; interiority and a gathering of wills) is proposed as a conceptual tool to critique Anak Dalita’s solutions to the squatter problem in Intramuros.